Differentiation-specific association of HP1alpha and HP1beta with chromocentres is correlated with clustering of TIF1beta at these sites - Bártová, Eva; Pacherník, Jirí; Kozubík, Alois; Kozubek, Stanislav (Histochemistry and cell biology, 2007)
Mammalian heterochromatin protein 1 (HP1alpha, HP1beta, HP1gamma subtypes) and transcriptional intermediary factor TIF1beta play an important role in the regulation of chromatin structure and function. Here, we investigated the nuclear arrangement of these proteins during differentiation of embryonal carcinoma P19 cells into primitive endoderm and into the neural pathway. Additionally, the differentiation potential of trichostatin A (TSA) and 5-deoxyazacytidine (5-dAzaC) was studied. In 70% of the cells from the neural pathway and in 20% of TSA-stimulated cells, HP1alpha and HP1beta co-localized and associated with chromocentres (clusters of centromeres), which correlated with clustering of TIF1beta at these heterochromatic regions. The cell types that we studied were also characterized by a pronounced focal distribution of HP1gamma. The above-mentioned nuclear patterns of HP1 and TIF1beta proteins were completely different from the nuclear patterns observed in the remaining cell types investigated, in which HP1alpha was associated with chromocentres while HP1beta and HP1gamma were largely localized in distinct nuclear regions. Moreover, a dispersed nuclear distribution of TIF1beta was observed. Our findings showed that the nuclear arrangement of HP1 subtypes and TIF1beta is differentiation specific, and seems to be more important than changes in the levels of these proteins, which were relatively stable during all the induced differentiation processes.
Keywords: Chromosomal Proteins, Non-Histone; DNA Methylation; homolog proteinu s chromoboxem 5; Recombinant Fusion Proteins; Cell Nucleus; centromera; Cell Line, Tumor; metylace DNA; konfokální mikroskopie; Centromere; western blotting; signální transdukce; buněčná diferenciace; Histone Deacetylase Inhibitors; Azacitidine; jaderné proteiny; imunohistochemie; buněčné jádro; Enzyme Inhibitors; Protein Subunits; rekombinantní fúzní proteiny; Hydroxamic Acids; Signal Transduction; podjednotky proteinů; Microscopy, Confocal; Blotting, Western; zelené fluorescenční proteiny; Animals; Transcription Factors; inhibitory histondeacetylas; transkripční faktory; Immunohistochemistry; Cell Differentiation; zvířata; kyseliny hydroxamové; Green Fluorescent Proteins; Chromobox Protein Homolog 5; chromozomální proteiny, nehistonové; nádorové buněčné linie; Decitabine; Nuclear Proteins; inhibitory enzymů; azacytidin; decitabin